Asian American communities and health :Context, research, policy, and action /Chau Trinh-Shevrin, Nadia Shilpi Islam, Mariano Jose Rey, editors ; foreword by Albert K. Yee. - Islam, Nadia Shilpi
Includes bibliographical references and indexes.